Analisis Logam Berat pada Air dan Sedimen di Perairan Pantai Pulau Singkep Kepulauan Riau - Jamalus Ishak; Bintal Amin; Thamrin ' (Berkala Perikanan Terubuk, 2014)
ABSTRACTAnalysis of the content of heavy metals Cu, Pb and Zn in seawater, sediment and snails (C. obtusa) in Singkep island held on 28 November 2013 - 5 Januari 2014. All parameters measured water quality is still within tolerable limits for the survival of the aquatic organism. Samples of sea water, sediment and snails (C. obtusa) were taken from five stations with three replicates at each station. Heavy metals were analyzed in the KLH Pekanbaru laboratory using Atomic Abortion AA-7000 Shimadzu spectrophotometer. The results showed that the average content of heavy metals in Singkep waters is 0.0724 mg/l (Cu), 0.1285 mg/l (Pb)) and 0.11525 mg/l (Zn), the sediment was 10, 7513 ug/g (Cu), 25.7750 ug/g (Pb) and 34.1493 mg/g (Zn). Simple linear regression analysis indicates negative correlation between metals content in sea water and in sediment with Y = 12,864 –29,178X, r = 0,1616 (Cu), Y =26,181 – 3,1564X, r = 0,0632(Pb) ; and Y =45,479 - 61,286X, r = 0,2689 ( Zn).Keywords: heavy metals, water, sediment, Snail, Singkep Island